Metabolomics Study of the Hepatoprotective Effects and Mechanism of Aqueous Extract of Dendrobium nobile Lindl. on Alcoholic Liver Injury in Rats - Wang, Qiyi; Shan, Bingbing; Cheng, Weina; He, Tianmu; Chen, Kuan; Zhang, Jianyong; Duan, Cancan (Combinatorial Chemistry & High Throughput Screening, 2023)
Background: Dendrobium nobileLindl. (DNL) is effective for the treatment of alcoholic liver disease (ALD), but the underly mechanism is still unclear. Objectives: This research aimed to investigate the effects and mechanism of the aqueous extract of Dendrobium nobileLindl (AEDNL) in ALD rats based on a metabolomics approach. Materials and Methods: In this study, 18 Sprague-Dawley male rats were randomly divided into control, model, and AEDNL groups (n=six). Rats in the AEDNL group were given AEDNL (152 mg/kg) intragastric administration from the first day for 30 consecutive days. From day 15 to day 30, model and AEDNL groups were given 30% ethanol (10 ml/kg) after 4 h of daily administration. Then, serum and liver samples were collected for biochemical analysis, histopathological examination, and Ultra Performance Liquid Chromatography-Quadrupole Time-of-Flight Mass Spectrometry (UPLC-Q-TOF/MS) determination for metabolomic analysis. Results: Compared with the model group, the liver/body weight index and serum levels of TC, LDL-C, and TBIL in the AEDNL group were significantly decreased. Hepatocyte cord arrangement, hepatocyte balloon, and fat vacuolization were significantly improved in the AEDNL group. Metabolism profiles were changed in the model and AEDNL groups. Seven and two common differential metabolites (Guanosine3',5'-cyclic monophosphate, and Glutaric acid) were found in serum and liver, respectively. In addition, the hepatoprotective effect of AEDNL on ALD was related to steroid hormone biosynthesis, riboflavin metabolism, and glycerophospholipid metabolism. Conclusion: The research could provide novel evidence of the protective effects of AEDNL on ALD.
Keywords: hepatoprotective effects